The effects of dietary soybean hulls, wheat, crystalline amino acids and high protein corn dried distiller’s grains on nursery and/or finishing pig growth and carcass characteristics - Goehring, Devin Lynn (Kansas State University, 2013)
Six experiments using 3,659 nursery and finishing pigs were conducted to evaluate the effects of dietary soybean hulls and ingredient processing in corn-soybean meal or corn-soybean meal-DDGS diets on nursery and finishing performance. Experiment 1 tested increasing soybean hulls (0, 5, 10, 15, and 20%) and increasing soybean hulls decreased ADG and G:F. Experiment 2 evaluated increasing soybean hulls (0, 10, and 20%) in diets balanced or not for NE and showed reduced performance with increasing soybean hulls. Balancing for NE resulted in G:F similar to pigs fed the control. Experiments 3 and 4 evaluated increasing dietary soybean hulls in corn-soybean meal and corn-soybean meal-DDGS diets. Soybean hulls in either diet worsened G:F and improved caloric efficiency, suggesting current INRA (2004) values for soybean hulls underestimate their energy value. Experiment 5 evaluated 10 and 20% ground or unground soybean hulls in meal and pelleted diets. Caloric efficiency improved with high levels of soybean hulls. Pelleting improved ADG and eliminated negative effects on G:F with increasing soybean hulls, while grinding soybean hulls reduced performance. Experiment 6 tested increasing ground and unground soybean hulls (0, 7.5, and 15%). Increasing soybean hulls worsened G:F, carcass yield, and hot carcass weight. Grinding soybean hulls to finer particle sizes did not improve ADG and worsened G:F. Experiments 7 and 8 evaluated the replacement of corn with wheat and crystalline amino acids in nursery and finishing pig diets. Replacing 50% of corn with wheat did not affect growth performance in either nursery or finishing; however 100% replacement of corn with wheat reduced performance. In addition, feeding wheat improved carcass fat IV, while use of high levels of crystalline amino acids in wheat-based diets did not influence performance in either study. Experiment 9 evaluated the replacement of soybean meal with high-protein dried distiller’s grains with solubles and crystalline amino acids. High-protein DDGS and crystalline AA can replace 50% of the SBM in finishing diets without negatively affecting performance or carcass yield. Replacing 100% of SBM with high-protein DDGS reduced growth rate, but increasing crystalline AA levels can help mitigate negative effects on carcass yield and fat IV.
Keywords: DDGS; Growth; Pig; Soybean hulls; Wheat; Animal Sciences (0475); Nutrition (0570)